ANTIBIOTIC RESISTANCE GENES IN FRESHWATER ENVIRONMENT: SOURCES, FATE, ECOLOGICAL IMPACT AND CLINICAL RELEVANCE - Ndukwe, N. N.; Ibrahim, H. I. (FUDMA JOURNAL OF SCIENCES, 2024)
Global public health is seriously threatened by antibiotic resistance, making the identification of environmental reservoirs of antibiotic resistance genes (ARGs) a crucial area of study. Freshwater ecosystems are particularly important for the spread of ARGs because of the intricate interactions between diverse microbial populations, human activities, and various antibiotic contamination sources. This review aims to offer a thorough understanding of the origin, progression, environmental impact, and medical significance of ARGs in freshwater environment. ARGs enter freshwater systems through various means, including the release of treated and untreated wastewater, agricultural drainage, and discharge of antibiotics and their byproducts. Once introduced, ARGs can endure freshwater environments through processes, such as horizontal gene transfer, co-selection, and biofilm formation. Moreover, the presence of ARGs in freshwater ecosystems has significant ecological consequences, affecting microbial diversity, ecosystem functions, and biogeochemical processes. The clinical relevance of ARGs in freshwater environments is a matter of concern. These genes can be transmitted to disease-causing bacteria, resulting in treatment failure and proliferation of infections that are resistant to multiple drugs. Additionally, the potential for ARGs to contaminate drinking water supplies raises concerns regarding human health. To develop effective strategies for combating the proliferation of antibiotic resistance, it is crucial to understand the behavior of ARGs in freshwater ecosystems. This review emphasizes the necessity of enhanced wastewater treatment technologies, responsible antibiotic usage, and sustainable farming practices to decrease the release and persistence of ARGs in freshwater ecosystems, ultimately protecting public health and maintaining the ecological balance of these vital habitats.